Covalent conjugation with (−)-epigallo-catechin 3-gallate and chlorogenic acid changes allergenicity and functional properties of Ara h1 from peanut. (30th November 2020) - He, Weiyi; Zhang, Tingting; Velickovic, Tanja Cirkovic; Li, Shuiming; Lyu, Yansi; Wang, Linlin; Yi, Jiang; Liu, Zhigang; He, Zhendan; Wu, Xuli
Highlights: Polyphenol covalent conjugation induced Ara h1 conformational changes. Ara h1-polyphenols may reduce the allergenicity of Ara h1. Ara h1-polyphenols increased pepsin digestibility and antioxidant activity. Abstract: Ara h1 is a major allergen from peanut. We investigated the effect of covalent conjugation of Ara h1 and dietary polyphenols on allergenicity and functional properties of Ara h1. Enzyme-linked immunosorbent assay revealed that the covalent conjugation of dietary polyphenols significantly reduced the IgE binding capacity of Ara h1. Covalent binding of dietary polyphenols with Ara h1 reduced histamine release by 40% in basophils. The decreased IgE binding capacity of Ara h1 could be ascribed to changes in protein conformation. The IgE epitope of Ara h1 might be blocked by polyphenols at the binding site. Analysis of pepsin digestion of Ara h1–polyphenol conjugates indicated that the covalent binding increased pepsin digestibility and reduced IgE binding capacity. Furthermore, covalent conjugation of Ara h1 with polyphenols decreased denaturation temperature and increased antioxidant activity. Ara h1 conjugated with polyphenols may be a promising approach for reducing the allergenicity of Ara h1.